Odpowiedzi

2010-03-30T17:09:24+02:00
PC=Pp+Pb
Pp=a²
pp=6²=36
Pb=4*a*h/2
h²+3²=4²
h²+9=16
h=√7
Pb=4*6*√7/2=12√7
Pc=36+12√7
Chyba dobrze a ajak źle to sory
2010-03-30T17:14:35+02:00
Pc= Pp+Pb
Pc= 36 + 12√7 cm²

Pp= a²= 36cm²
Pb= 4× 3√7 = 12√7cm²

Pole Pb:
½a×h= 3×√7=3√7

h trójkąta z Pb:
3²+h²=4²
9+h²=16
h=√7



2010-03-30T17:21:39+02:00
Pp = 6 * 6
Pp = 36 cm ²

3 ² + b ² = 4 ² (twierdzenie pitagorasa)
9 + b ² = 16 / -9
h ² = 7
h = √7

Psb = ½ * a * h
Psb = ½ * 6 * √7
Psb = 3√7

Pb = 4 * 3√7
Pb = 12 √7

Pc = Pp + Pb
Pc = 36 + 12 √7
Pc = 36 + 12 √7 [cm²]